Isochronal sintering of the blended elemental Ti-35Nb alloy - Santos, D. R. [UNESP]; Pereira, Marcelo dos Santos [UNESP]; Cairo, C. A. A.; Graca, M. L. A.; Henriques, V. A. R. (Elsevier B.V. Sa, 2008)
Titanium alloy parts are ideally suited for advanced aerospace systems and surgical implants because of their unique combination of high specific strength at both room temperature and moderately elevated temperature, in addition to excellent corrosion resistance. In this work, results of the Ti-35Nb alloy sintering are presented. This alloy, due to its lower modulus of elasticity and high biocompatibility, is a promising candidate for surgical and aerospace applications. Samples were produced by mixing of initial metallic hydride powders followed by uniaxial and cold isostatic pressing with subsequent densification by isochronal sintering between 700 and 1500 degrees C, in vacuum. Sintering behavior was studied by means of microscopy and density. Sintered samples were characterized for phase composition, microstructure and microbardness by X-ray diffraction, scanning electron microscopy and Vickers indentation, respectively. Samples sintered at high temperatures display a fine plate-like a structure and intergranular P. A few remaining pores are still found, and density above 97% for specimens sintered at 1500 degrees C is reached. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: powder metallurgy; titanium alloys; modulus of elasticity; near net shape